2012
DOI: 10.1002/glia.22396
|View full text |Cite
|
Sign up to set email alerts
|

KSRP: A checkpoint for inflammatory cytokine production in astrocytes

Abstract: Chronic inflammation in the central nervous system (CNS) is a central feature of many neurodegenerative and autoimmune diseases. As an immunologically competent cell, the astrocyte plays an important role in CNS inflammation. It is capable of expressing a number of cytokines such as tumor necrosis factor alpha (TNF-α) and interleukin-1 beta (IL-1β) that promote inflammation directly and through the recruitment of immune cells. Checkpoints are therefore in place to keep tight control over cytokine production. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 53 publications
1
48
0
1
Order By: Relevance
“…RBPs can dramatically affect target mRNA and protein levels. In astrocytes, knockdown of HuR led to a 30–40% attenuation of factors relevant to ischemia such as TNF-α, IL-1β, and MMP-12, whereas knockout of KSRP led to significant increases [13, 20, 21, 24, 26]. These observations provided the basis for our hypothesis that HuR affects secondary tissue injury in experimental ischemic stroke.…”
Section: Introductionmentioning
confidence: 68%
“…RBPs can dramatically affect target mRNA and protein levels. In astrocytes, knockdown of HuR led to a 30–40% attenuation of factors relevant to ischemia such as TNF-α, IL-1β, and MMP-12, whereas knockout of KSRP led to significant increases [13, 20, 21, 24, 26]. These observations provided the basis for our hypothesis that HuR affects secondary tissue injury in experimental ischemic stroke.…”
Section: Introductionmentioning
confidence: 68%
“…Multiple components of inflammatory signaling were affected including IL‐6 , IL‐1α , IL‐1β , and Ptgs ( Cox −2), and two amplifiers of cytokine production, Trem‐1 and TremL4 . We previously observed that Trem1 is regulated in astrocytes by KH‐type splicing regulatory protein (KSRP), another ARE‐binding protein which promotes degradation and reduced translation of its target mRNAs (King and Chen, ; Li et al, ). Of the classic factors associated with the M2 phenotype, arginase 1 was significantly attenuated by nearly fourfold (Supporting Information, Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Dhamija et al reported that as many as 50 mRNAs that are targets of KHSRP are enriched in polysomes after KHSRP knock‐down and among these mRNAs are those encoding IL6, IL23A, and TNF. Also studies performed in Khsrp −/− astrocytes support a role of KHSRP in TNF and IL1B translation.…”
Section: Role Of Khsrp In the Immune Responsementioning
confidence: 99%
“…The analysis of KHSRP knockout mice revealed that IFNA and IFNB are upregulated in cells derived from Khsrp −/− mice because of enhanced mRNA half‐life and this regulation explains the robust response of Khsrp −/− mice to viral infections (see Section Role of KHSRP in Viral Infections ). Further, Li et al observed that the expression of TNF and IL1B significantly increased in astrocytes derived from Khsrp −/− mice when compared to wild‐type littermate. Considering that IFNs and cytokines play a crucial role in the pathogenesis of autoimmune diseases, the elucidation of KHSRP function in restraining their expression in immune cells may lead to the development of therapeutic strategies for these pathologies.…”
Section: Role Of Khsrp In the Immune Responsementioning
confidence: 99%